Hubungan Kejadian Stunting dengan Perkembangan Motorik Kasar, Motorik Halus, dan Kognitif Pada Balita di Desa Wedoroanom Kecamatan Driyorejo Kabupaten Gresik - Hillary Shinta Pratiwi; Lini Anisfatus Sholihah (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
Based on the findings of the Indonesian Nutritional Status Study Survey (SSGI), the growth rate of stunting in toddlers in East Java reached 19.2%. The prevalence of stunting in Wedoroanom Village is included in the highest category in Driyorejo District, Gresik Regency, reaching 36%. The purpose of this study was to describe the prevalence of stunting, growth of gross motor skills, fine motor skills, and cognitive abilities, and to determine the relationship between these factors and the development of these skills in toddlers in Wedoroanom Village, Driyorejo District, Gresik Regency. This study used a cross-sectional technique and was quantitative. The sample consisted of 110 children aged between 12 and 60 months who were selected through a convenience sampling approach. Anthropometric measurements, interviews, and observations were used to obtain data. The chi-square test and odds ratio were used in data analysis to determine the relationship between variables. The study findings showed that the incidence of stunting and gross motor development were not related. However, there was a relationship between the incidence of stunting and cognitive and fine motor development. Chronic malnutrition, maternal education, maternal occupation, and history of exclusive breastfeeding are some of the factors that can cause developmental disorders in children. The findings of this study indicate that the incidence of stunting in Wedoroanom Village, Driyorejo District, Gresik Regency, is related to fine motor and cognitive development but not related to the development of gross motor functions.